Species diversity of Orchids in Bukit Barisan Selatan National Park, Lampung, Indonesia - ESTI MUNAWAROH; YUZAMMI YUZAMMI (Society for Indonesian Biodiversity, 2019)
Abstract. Munawaroh E, Yuzammi. 2019. Species diversity of Orchids in Bukit Barisan Selatan National Park, Lampung, Indonesia. Biodiversitas 20: 343-349. Orchids, belonging to the family Orchidaceae, are well known ornamental plants due to their beautiful flowers and varied colors. The members of this family have received more scientific attention than other plant families because of their unique botanical features and economic value. This study was conducted to explore and record the species diversity of Orchidaceae in Sumatera, especially in the Bukit Barisan Selatan National Park (BBSNP), Lampung, Indonesia. This research was carried out from 2011 to 2014 at four locations, namely Kubu Perahu Resort, Sukaraja Atas Resort, Pugung Tampak Resort and Sekincau Resort, using purposive sampling method. A total of 132 species belonging to 52 genera of orchids have been identified from BBSNP, Lampung, of which 37 genera are epiphytic orchids and 15 genera are terrestrial orchids. Two species namely, Vanda sumatrana and Grammatophyllum speciosum, have been recognized as protected species. Vanda sumatrana is also endemic to Sumatera. These orchids are also cultivated at Liwa Botanic Garden, as an ex situ conservation.